"Posterior Tibial Nerve" or "Tibial Nerve"? Improving the reporting in health papers. Issue 2 (5th December 2019) - Moretti, Eduarda; da Silva, Ivson Bezerra; Boaviagem, Alessandra; Barbosa, Leila; de Lima, Anna Myrna Jaguaribe; Lemos, Andrea
Abstract: Aims: The primary objective of this study is to identify which term is the most appropriate to use according to anatomical nomenclature: "posterior tibial nerve" or "tibial nerve." Furthermore, this paper intends to show how the use of these terms in papers indexed in important health databases is numerous and to describe the anatomical characteristics of such nerve, to improve future scientific publications. Methods: This is a descriptive study about the importance of standardizing the use of the terms "posterior tibial nerve" and "tibial nerve" and its anatomy. It comprises three phases: the first is a search in the main databases to identify the use of the terms "posterior tibial nerve" and "tibial nerve." The second phase refers to the consultation of international anatomical terminology to identify the most appropriate term to refer to the nerve, while the third phase is related to the study of the anatomy of this nerve. Results: The term "tibial nerve" is more commonly used, but the use of the term "posterior tibial nerve" is still very substantial. According to international anatomical terminology, the correct term is "tibial nerve, " which is a branch of the sciatic nerve. Conclusions: "Tibial nerve" is the term standardized by international anatomical terminology. The use of terms in accordance with Terminologia Anatomica is important to facilitate the process of teaching and learning, as well as to improve the reporting and interpretation of papers regarding health, and the evidence‐based clinical practice.